The phenomenon of bubu tradition in the cycle of time: Portrait of reciprocity in rural Madura - Halimatur Rizqiyah; Warsono Warsono; M. Jacky; Nasution Nasution (Faculty of Social and Political Science, Universitas Airlangga, 2021)
Bubu is a form of reciprocity that occurs in Madura generally and Langkap Village particularly. Generally, the exchange is made by the community as a form of “donations” to the celebration host. The host hopes for a return in the future. The reciprocal incident that occurred in Madura was not just a hope but more of an “obligation” to pay the “donation” or bubu that had been given on the previous occasion. This study seeks to describe the form and meaning of the bubu as well as to explain the changes that occur in the bubu phenomenon which used to be only in the form of voluntary donations into various forms of bubu with their meanings. The research design used was an ethnographic study with a moderate method where the researcher was occasionally directly involved in the tradition. The results of this study reveal several forms of bubu that occur in Langkap Village with different ways and meanings with the same motivation. The bubu given is a transaction of accounts payable and investment with the hope of a return in the future. More than that, there are social sanctions that will await if the bubu that have been given are not returned with the same value.